System, gesture, rhetoric: contexts for rethinking tintinnabuli in the music of Arvo Pärt, 1960-1990 - May, CJ (2016)
This thesis addresses critical strategies that have been used, or might be used, to approach Pärt's tintinnabuli music. It has three main objectives: to question prevalent narratives drawn around the tintinnabuli concept, to suggest interpretative frameworks that could yield fresh insights into that concept's 'meaning', and to introduce new and neglected materials to anglophone Pärt discourse. In studying the mediating role of the tintinnabuli scholar, I also confront some of the ethical challenges associated with research on living composers. This project places special emphasis on localised narratives of production and influence in Pärt's music, and draws extensively on Estonian primary source material. A major hermeneutic guide has been the composer's 1994 description of seeking ‘the appropriate system for the gesture’, and this idea figures in each of the four main chapters. Chapter 1 describes and questions existing knowledge around tintinnabuli, approaching this task through a study of "Wenn Bach Bienen Gezüchtet Hätte …", a work chosen for its critically fertile 'cusp’ status. Chapter 2 concentrates on Pärt's explorations of 'Soviet serialism' from 1960-3, engaging with withdrawn and film scores in addition to the well-known "Nekrolog". I discuss this music in terms of a complex freedom-constraint interplay, and suggest links to the tintinnabuli style. Taking "Sarah Was Ninety Years Old" as a case study, Chapter 3 turns to listener-oriented frameworks of musical meaning. I offer an experiential reading of the piece that places tintinnabuli in dialogue with body-based theories of cognition. Lastly, Chapter 4 addresses texted tintinnabuli. I build up a reading of "Miserere" in terms of 'musical rhetoric', comparing Pärt's compositional strategies to those used by Josquin des Prez in the 1503 motet "Miserere Mei, Deus". I also consider the implications of music-rhetorical analogy for wider understandings of the 'tintinnabuli' concept.